2021
DOI: 10.3390/nu13072139
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, Copper, Zinc Concentrations and Cu/Zn, Cu/Se Molar Ratios in the Serum of Patients with Acute Ischemic Stroke in Northeastern Poland—A New Insight into Stroke Pathophysiology

Abstract: Background: In recent years, trace elements (TEs) have gained considerable attention in the course of treatment and diagnosis of ischemic stroke. The purpose of the conducted research was to determine the trace mineral status (Se, Cu, Zn, Cu/Zn ratio, and Cu/Se ratio) in patients with acute ischemic stroke compared to the population of healthy people in the northeastern region of Poland. Materials and methods: 141 patients with acute ischemic stroke (AIS) and 69 healthy control subjects were examined. The seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 90 publications
(131 reference statements)
1
36
0
Order By: Relevance
“…Essential elements are vital to human health, as they are involved in a multitude of biochemical reactions in cells [2,6]. Because of their fundamental roles in the brain, many studies have investigated Mg, Zn, Se, Fe, and Cu [2,6,15,17]. Mg is the most abundant intracellular cation and exhibits a wide range of biological activities, including anti-oxidant functions, energy production, modulation of glucose transport across the cell membrane, calcium antagonist activity, and anti-inflammatory effects [6,21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Essential elements are vital to human health, as they are involved in a multitude of biochemical reactions in cells [2,6]. Because of their fundamental roles in the brain, many studies have investigated Mg, Zn, Se, Fe, and Cu [2,6,15,17]. Mg is the most abundant intracellular cation and exhibits a wide range of biological activities, including anti-oxidant functions, energy production, modulation of glucose transport across the cell membrane, calcium antagonist activity, and anti-inflammatory effects [6,21].…”
Section: Discussionmentioning
confidence: 99%
“…Zn is involved in a variety of biological functions such as brain development, wound healing, anti-oxidation, and anti-inflammation [1,2,15]. An investigation showed that Zn exerts antioxidant effects to protect cells from ROS attack to prevent further deleterious lipid peroxidation [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations